RNA/DNA co-analysis from human skin and contact traces – results of a sixth collaborative EDNAP exercise. (May 2015) - Haas, C.; Hanson, E.; Banemann, R.; Bento, A.M.; Berti, A.; Carracedo, Á.; Courts, C.; Cock, G. De; Drobnic, K.; Fleming, R.; Franchi, C.; Gomes, I.; et al.
Highlights: EDNAP organized a collaborative exercise on RNA/DNA co-analysis of skin samples. 8 skin and 3 HKG markers were tested for specificity, sensitivity and applicability. LCE1C, LOR and B2M were detected in most contact traces, detection of the other markers was inconsistent. LCE1C and LOR markers showed some cross-reactivity with non-skin sample types. With contact traces the method reaches the detection limit. Abstract: The European DNA profiling group (EDNAP) organized a sixth collaborative exercise on RNA/DNA co-analysis for body fluid/tissue identification and STR profiling. The task was to identify skin samples/contact traces using specific RNA biomarkers and test three housekeeping genes for their suitability as reference genes. Eight stains, a skin RNA dilution series and, optionally, bona fide or mock casework samples of human or non-human origin were analyzed by 22 participating laboratories using RNA extraction or RNA/DNA co-extraction methods. Two sets of previously described skin-specific markers were used: skin1 pentaplex (LCE1C, LCE1D, LCE2D, IL1F7 and CCL27) and skin2 triplex (LOR, KRT9 and CDSN) in conjunction with a housekeeping gene, HKG, triplex (B2M, UBC and UCE). The laboratories used different chemistries and instrumentation. All laboratories were able to successfully isolate and detect mRNA in contact traces (e.g., human skin, palm-, hand- and fingerprints, clothing, car interiors, computer accessories and electronic devices). The simultaneous extraction of RNA and DNA provides an opportunity for positive identification of the tissue source of origin by mRNA profiling as well as a simultaneous identification of the body fluid donor by STR profiling. The skin markers LCE1C and LOR and the housekeeping gene marker B2M were detected in the majority of contact traces. Detection of the other markers was inconsistent, possibly due to the low amounts and/or poor quality of the genetic material present in shed skin cells. The results of this and the previous collaborative RNA exercises support RNA profiling as a reliable body fluid/tissue identification method that can easily be combined with current STR typing technology.